Cerebral vascular findings in PAPA syndrome: cerebral arterial vasculopathy or vasculitis and a posterior cerebral artery dissecting aneurysm. (24th June 2015) - Khatibi, Kasra; Heit, Jeremy J; Telischak, Nicholas A; Elbers, Jorina M; Do, Huy M
Abstract : A young patient with PAPA (pyogenic arthritis, pyoderma gangrenosum, and acne) syndrome developed an unusual cerebral arterial vasculopathy/vasculitis (CAV) that resulted in subarachnoid hemorrhage from a ruptured dissecting posterior cerebral artery (PCA) aneurysm. This aneurysm was successfully treated by endovascular coil sacrifice of the affected segment of the PCA. The patient made an excellent recovery with no significant residual neurologic deficit.